The Effectiveness of Training on Utilization of Internet Technology to Increase Sales of Home Industry Products on the Island of Lombok - Heroe Santoso; Basirun Basirun; Raisul Azhar; Husain Husain (Jurnal Varian, 2020)
The home industries in Lombok Island do not fully understand using internet technology in marketing their products. This study aims to see the effectiveness of the use of internet technology to increase the sales results of home industry products on the island of Lombok. Sampling using a questionnaire spread over 4 classes. Each class consists of 40 people. Furthermore, from the data obtained, a description, normality test, and homogeneity test were carried out. The method used in this research is the Wilcoxon test using the SPSS program. The results showed that after the training was held, there was an increase in understanding of the use of the internet as a means of increasing sales of home industrial products on the island of Lombok.